PREFERENSI MANAJEMEN LABA AKRUAL ATAU MANAJEMEN LABA RIIL DALAM AKTIVITAS TAX SHELTER - Geraldina, Ira (UI Scholars Hub, 2013)
This study aims to examine the effect of accrual or real earnings management on the possibility of companies involved in tax shelter activities by using Surat Ketetapan Pajak Kurang Bayar (notice of tax deficiency) as a proxy to measure the tax shelter. By using a sample of companies who received Surat Ketetapan Pajak Kurang Bayar (notice of tax deficiency) in manufacturing industry and listed in Indonesia Stock Exchange during the period 2001-2010, this study finds that the company tends to favor accrual earnings management for decreasing possibility of aggressive tax shelter activities. This finding is not supporting the hyphotesis. Real earnings management via abnormal operating cash flows and abnormal discretionary production increasing possibility of aggressive tax shelter activities. Both findings are supporting the hypothesis. This study also finds that both practices of accrual earnings management or real earnings management have substitute effect in explaining the possibility of companies involved in tax shelter activities.